The Role of ATP-Binding Cassette Proteins in Stem Cell Pluripotency - Prince Saini; Sharath Anugula; Yick W. Fong (Biomedicines, 2023)
Pluripotent stem cells (PSCs) are highly proliferative cells that can self-renew indefinitely in vitro. Upon receiving appropriate signals, PSCs undergo differentiation and can generate every cell type in the body. These unique properties of PSCs require specific gene expression patterns that define stem cell identity and dynamic regulation of intracellular metabolism to support cell growth and cell fate transitions. PSCs are prone to DNA damage due to elevated replicative and transcriptional stress. Therefore, mechanisms to prevent deleterious mutations in PSCs that compromise stem cell function or increase the risk of tumor formation from becoming amplified and propagated to progenitor cells are essential for embryonic development and for using PSCs including induced PSCs (iPSCs) as a cell source for regenerative medicine. In this review, we discuss the role of the ATP-binding cassette (ABC) superfamily in maintaining PSC homeostasis, and propose how their activities can influence cellular signaling and stem cell fate decisions. Finally, we highlight recent discoveries that not all ABC family members perform only canonical metabolite and peptide transport functions in PSCs; rather, they can participate in diverse cellular processes from genome surveillance to gene transcription and mRNA translation, which are likely to maintain the pristine state of PSCs.